Radiations and Extinctions of Maastrichtian Rudist bivalve and Benthic Foraminifera of Aqra Formation Kurdistan Region Northern Iraq - Al-Dulaimi, Salam (Iraqi Journal of Science, 2023)
During the Maastrichtian, the rudists and benthic foraminifera of Aqra Formation underwent two major radiations, the first beginning in early Early Maastrichtian and peaking in the late Early Maastrichtian, and sconed extending from the early Late Maastrichtian to a late Late Maastrichtian peak.The radiations were punctuated and separated by prominent extinction episodes, fit with global Maastrichtian mass extinction.The high level of rudist, endemism [90%] allows definition of true regional origination and extinction pattern; these may represent global pattern for rudists. Radiation and extinction patterns in the northern Iraq [Kurdistan Region] can be variously related to relative sea level fluctuation and the rate of food and clastic sediments supply.The two Maastrichtian extinctions of Aqra Formation is true extinctions in that they occur during low or zero origination rates among rudists.